Plant Parts - Joela Jacobs (Plant Perspectives)
While the natural sciences and the humanities were not always as separate as they appear today, language has connected them inextricably throughout history. Terminology for plant parts such as root, leaf, stem, flower and fruit have been operative across disciplines both as references to actual vegetal matter and as tropes that carry and continue to take on new metaphorical, allegorical, symbolic and topological meanings that go beyond the strictly botanical. By exemplarily examining five such tropes, this article maps these discursive networks of meaning and their phytopoetic resonances, showing how plants have shaped human thought and culture.